2003
DOI: 10.1021/la020670d
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbons Chemically Modified by Concentrated H2SO4 for the Adsorption of the Pollutants from Wastewater and the Dibenzothiophene from Fuel Oils

Abstract: The surface properties, porosities, and adsorption capacities of activated carbons (AC) are modified by the oxidation treatment using concentrated H2SO4 at temperatures 150−270 °C. The modified AC was characterized by N2 adsorption, base titration, FTIR, and the adsorption of iodine, chlorophenol, methylene blue, and dibenzothiophene. The treatment of AC with concentrated H2SO4 at 250 °C greatly increases the mesoporous volume from 0.243 mL/g to 0.452 mL/g, specific surface areas from 393 m2/g to 745 m2/g, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
147
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(155 citation statements)
references
References 45 publications
(77 reference statements)
7
147
0
1
Order By: Relevance
“…Scientific efforts focus on oxidation [1,2], photoxidation [3,4] or adsorption . The adsorption based methods applied activated alumina [7,8], zeolites [9], and activated carbons [7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] as adsorbents. The results obtained on the latter materials seem promising [12,22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific efforts focus on oxidation [1,2], photoxidation [3,4] or adsorption . The adsorption based methods applied activated alumina [7,8], zeolites [9], and activated carbons [7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] as adsorbents. The results obtained on the latter materials seem promising [12,22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicated that the oxidation of a carbon surface enhances their performance in the desulfurization process [15, 17, 18, 21-23, 26, 27] owing to acid-base interactions of thiophenes with acidic oxygen groups of activated carbons [15,18,22,23,27]. Presence of copper [16,24], iron [24] or silver [29] compounds on the carbons was also shown as beneficial for the selectivity of separation.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction time for a complete conversion can be shortened to 30 and 8 min as the reaction temperature is elevated to 60 and 90°C, respectively [20]. It is worthwhile to point out that these organic sulfides and their derivatives are the most refractory sulfurcontaining molecules present in diesel and are extremely difficult to remove using conventional hydrodesulfurization (HDS) [22][23][24]. This provides the possibility for selective oxidation of sulfides present in fuel oils combined with extraction for ultra-deep desulfurization [20].…”
Section: Selective Oxidation Of Real Diesel In W/o Emulsionmentioning
confidence: 99%
“…Activated carbons are carbonaceous materials that can be distinguished from elemental carbon by the oxidation of the carbon atoms found on the outer and inner surfaces (Mattson and Mark 1971). These materials are characterized by their extraordinary large specific surface areas, well-developed porosity, and tunable surface containing functional groups (Baker et al 1992;Jiang et al 2003). For these reasons, activated carbons are widely used as adsorbents for the removal of organic chemicals and metal ions of environmental or economic concern from air, gases, potable water, and wastewater (El-Hendawy 2003).…”
Section: Introductionmentioning
confidence: 99%